Zum Vorkommen der Gattung Badister Clairville in Mecklenburg (Coleoptera: Carabidae). - Müller, Gerd (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Periodical studies in eastern Mecklenburg established the occurrence of Badister bipustulatus Fabricius, Badister lacertosus Sturm, Badister sodalis Duftschmid and Badister dilatatus Chaudoir. It was found that the various Badister species differ in their ecological requirements. Badister lacertosus Sturm was determined as a species propria in the area under consideration and characterized as a spring animal with autumn life.